Caracterización agromorfológica de tres poblaciones ex situ de bijao (calathea lutea a.) para establecer parámetros de cultivo - Cuenca Caraguay, Luis Fernando (Machala : Universidad Técnica de Machala, 2022)
The cultivation of bijao has potential use in the agro-industrial sector, because the foliage is used as a raw material, in the production of protectors, utensils, candy packaging, it is used in a biodegradable way because it does not cause damage to the environment. In Ecuador, the lack of knowledge and information of this species about its chemical properties and the benefits it offers to be an economic alternative. The area where the research was carried out was in the Santa Inés Experimental Farm, belonging to the Faculty of Agricultural Sciences, Technical University of Machala, located in the canton of Machala, province of El Oro. The objective of the work was to characterize the behavior of three populations ex -situ of bijao, through the description of agromorphological parameters in order to use its leaves in the production of protectors for organic banana bunches. A completely randomized design was used, where three plots were built, with a total of 80 plants per experimental unit. Three cultivars of bijao were used as plant matter, which were collected within the province of El Oro. The localities are La Avelina, Casacay, and Pejeyacu, where a total of 240 plants were planted. The measured variables were; foliar emission (h/s), length and width of the 3rd leaf (cm), total leaves, leaf area (m2), plant height (cm), leaves with wax on the underside, color of new leaf and of the lower leaves, rhizomes per plant, weight of the 3rd leaf (g), total weight of leaves per plant (g), viable leaves per plant at harvest time, number of hands on the bunch, weight of the bunch, rachis and fruit (lb), sum of the fingers of the second and last hand, incidence of cochineal and red spot (%), presence of sooty mold, as well as physical and mechanical damage (%). In order to know whether or not there are significant statistical differences between the vegetative material from the three localities, an analysis of variance of an intergroup factor and the Tukey test were carried out to establish between which differences or similarities are present. Through the analysis of the agromorphological variables of the bijao crop, it was obtained that the vegetative material from La Avelina presented the highest and statistically significant values in the greater number of the variables evaluated in relation to those from Pejeyacu and Casacay, which It may be associated with the similar edaphoclimatic conditions that occur in the Faculty of Agricultural Sciences and La Avelina. Regarding the production of useful leaves, the best average was presented in the plants collected in Pejeyacu (7), which showed statistically significant differences compared to the averages presented in the plants from La Avelina (6) and Casacay (6). ). The efficiency of the use of biodegradable protectors in the preventive quality of organic banana bunches did not present significant differences in the production variables evaluated, demonstrating that regardless of the origin, their use can replace plastic protectors, and in this way contribute to take care of the environment.
El cultivo de bijao tiene potencial uso en el sector agroindustrial, porque se utiliza el follaje como materia prima, en la elaboración de protectores, utensilios, empaques de dulces, se emplea de manera biodegradable debido que no causa daños al medio ambienté. En ecuador la falta de conocimientos e información de esta especie sobre sus propiedades químicas y los beneficios que ofrece para ser una alternativa económica. El área donde se efectuó la investigación fue en la Granja Experimental Santa Inés, perteneciente, Facultad de Ciencias Agropecuarias, Universidad Técnica de Machala, ubicada en el cantón Machala, provincia de El Oro. El objetivo del trabajo fue caracterizar el comportamiento de tres poblaciones ex-situ de bijao, mediante la descripción de parámetros agromorfológicas con el fin del aprovechamiento de sus hojas en la elaboración de protectores para los racimos de banano orgánico. Se usó un diseño completamente aleatorizado, donde se construyeron tres parcelas, con un total de 80 plantas por unidad experimental. Se utilizaron como materia vegetal tres cultivares de bijao, las cuales fueron recolectadas dentro de la provincia de El Oro. Las localidades son La Avelina, Casacay, y Pejeyacu, las cuales se plantaron un total de 240 plantas. Las variables medidas fueron; emisión foliar (h/s), largo y ancho de la 3ra hoja (cm), hojas totales, área foliar (m2), altura de la planta (cm), hojas con cera en el envés, color de hoja nueva y de las hojas bajeras, rizomas por planta, peso de la 3ra hoja (g), peso total de las hojas por planta (g), hojas viables por planta al momento de la cosecha, número de manos del racimo, peso del racimo, raquis y de la fruta (lb), sumatoria de los dedos de la segunda y última mano, incidencia de cochinilla y mancha roja (%), presencia de fumagina, así como, daños físicos y mecánicos (%). Para conocer si existen o no diferencias estadísticas significativas entre el material vegetativo procedente de las tres localidades se efectuó un análisis de varianza de un factor intergrupos y la prueba de Tukey para establecer entre cuales se presentan diferencias o similitudes. Mediante el análisis de las variables agromorfológicas del cultivo de bijao, se obtuvo que el material vegetativo procedente de La Avelina presento los valores más altos y significativos estadísticamente en la mayor cantidad de las variables evaluadas en relación a las procedentes de Pejeyacu y Casacay, lo que puede estar asociado a las condiciones edafoclimáticas similares que se presentan en la Facultad de Ciencias Agropecuarias y La Avelina. En lo que respecta a producción de hojas útiles, la mejor media se presentó en las plantas recolectadas en Pejeyacu (7), que mostraron diferencias estadísticamente significativas en comparación a las medias presentadas en las plantas procedentes de La Avelina (6) y Casacay (6). La eficiencia del uso de protectores biodegradables en la calidad preventiva de los racimos de banano orgánico, no presentó diferencias significativas en las variables de producción evaluadas, demostrando que sin importar el origen su uso puede reemplazar a los protectores plásticos, y de esta forma contribuir a cuidar el medio ambiente.
Keywords: BIJAO; PROTECTORES BIODEGRADABLES; VARIABLES AGROMORFOLÓGICAS; PRODUCCIÓN